Comparative analysis of Electrospun PLA fibers incorporating bioactive glass nanoparticles: morphological, biological, and osteogenic properties for bone regeneration - Souza, Brunna da Silva Nobrega [UNESP]; de Siqueira, Lilian [UNESP]; Fernandes, Marina Santos [UNESP]; de Souza, Joyce Rodrigues [UNESP]; Kukulka, Elisa Camargo [UNESP]; Grisante, Letícia Adrielly Dias [UNESP]; Campos, Tiago Moreira Bastos; de Vasconcellos, Luana Marotta Reis [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Elsevier, 2025)
Polylactic acid (PLA) is widely studied for bone repair due to its biodegradability, biocompatibility, and bioresorbability. However, its limited bioactivity and hydrophobic surface hinder optimal cell interaction and integration. Incorporating bioactive glass (BG) particles into PLA scaffolds via electrospinning and electrospray techniques has emerged as a promising strategy to improve biological performance. This study aimed to fabricate and characterize PLA scaffolds, both with incorporated and surface-coated BG, and to assess their osteogenic potential for tissue engineering applications. Scaffold morphology was evaluated by scanning electron microscopy, and biological performance was assessed through in vitro assays using mesenchymal stem cells derived from Wistar rat bone marrow. Cell viability, total protein content, alkaline phosphatase (ALP) activity, and mineralized nodule formation were analyzed. The scaffolds displayed porous, interconnected structures with fiber diameters influenced by BG incorporation method. All groups demonstrated cytocompatibility, while scaffolds containing BG both incorporated and sprayed-showed significantly higher ALP activity, suggesting enhanced osteogenic differentiation. Mineralization nodules further confirmed the induction of osteogenesis. These findings highlight the potential of PLA/BG composite scaffolds, especially when functionalized via combined electrospinning and electrospray methods, as a promising platform for bone tissue engineering.